Influência da complexidade estrutural de macrófitas aquáticas sobre a diversidade de organismos perifíticos. - Fulone, Leandro Junio (2008)
Aquatic macrophytes play an important role on the structure and functioning of aquatic ecosystems increasing the habitat heterogeneity and favoring a high biodiversity. In this way, this study evaluated the influence of structural complexity from different species of aquatic macrophytes on the structure of periphytic testate amoebae, rotifers, cladocerans and copepods. The macrophytes were categorized along a growing gradient of complexity to test the hypothesis that the species richness and diversity, beyond the abundance, increase positively along this gradient. All groups presented a concordant increase between the complexity and abundance values. The species richness varied among the different complexity degrees, and, in general, high values were recorded at more complex macrophytes. The total species diversity, the testate amoebae and rotifers diversity were also significantly correlated to structural complexity gradient. The relationships between the attributes of different assemblages and the complexity degree of aquatic macrophytes were related to the size and life history of studied groups. Our results allow arguing that not only structural complexity, but also the habitat heterogeneity is determinant for the maintenance of biodiversity from aquatic environments.